2019
DOI: 10.1111/desc.12764
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ early book reading to children: Relation to children's later language and literacy outcomes controlling for other parent language input

Abstract: It is widely believed that reading to preschool children promotes their language and literacy skills. Yet, whether early parent-child book reading is an index of generally rich linguistic input or a unique predictor of later outcomes remains unclear. To address this question, we asked whether naturally occurring parent-child book reading interactions between 1 and 2.5 years-of-age predict elementary school language and literacy outcomes, controlling for the quantity of other talk parents provide their children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 52 publications
5
99
2
8
Order By: Relevance
“…In addition to language exposure, home literacy practices are also associated with subsequent verbal and literacy skills during preschool and school-age (e.g., [28][29][30][31]), highlighting the important role of the environment. Moreover, emergent literacy skills are then further deepened through instruction once the child starts school and reciprocally influence language development, such as vocabulary [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to language exposure, home literacy practices are also associated with subsequent verbal and literacy skills during preschool and school-age (e.g., [28][29][30][31]), highlighting the important role of the environment. Moreover, emergent literacy skills are then further deepened through instruction once the child starts school and reciprocally influence language development, such as vocabulary [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Further, they found that there was also not a difference based on hearing levels. However, it is documented that the volume of exposure to accessible auditory input produces great variability in results related to children's language acquisition [46,52]. Taken together, these findings again point to language access and interactions using meaningful language as the salient variables, not merely access to sound.…”
Section: Spoken Language Development and Instructionmentioning
confidence: 92%
“…For example, in a study by Figueras and colleagues [51], researchers found strong correlations between executive functioning and spoken language, but no difference between children who used CIs and those that did not. Similarly, Jones and colleagues [52] found that there was no difference in narrative performance between deaf children using hearing aids and those with CI. Further, they found that there was also not a difference based on hearing levels.…”
Section: Spoken Language Development and Instructionmentioning
confidence: 93%
See 1 more Smart Citation
“…Yurtdışında birlikte okumaya yönelik pek çok araştırma olmasına karşın (Kim ve Anderson, 2008;Tercanlı Metin ve Gökçay, 2014), birlikte okuma ülkemizde görece yeni bir yöntem olduğundan (Kotaman, 2007), son yıllarda ve sınırlı sayıda araştırmaya konu olmuştur (Ergül ve diğerleri, 2015;Tercanlı Metin ve Gökçay, 2014). Yurtiçi ve yurtdışında yapılan araştırmalar, birlikte okumanın çocukların okuma ilgisi ve alışkanlığı kazanmalarında (Bracken ve Fischel, 2008;Demir-Lira, Applebaum, Goldin-Meadow ve Levine, 2018;Duursma, 2014;Kotaman, 2008;Öztürk, Hill ve Yates, 2016;Shahaeian ve diğerleri, 2018;Vandermaas-Peeler, Sassine, Price ve Brilhart, 2011), erken okuryazarlık ve dil gelişiminde (Aram ve Shapira, 2012;Bıçakçı, Er ve Aral, 2018;Bracken ve Fischel, 2008;Demir-Lira ve diğerleri, 2018;Duursma, 2014;Ergül ve diğerleri, 2015;Kotaman, 2008Kotaman, , 2009Levy, Hall ve Preece, 2018;Lin, Stephanie ve Sabrina, 2015;Lyytinen, Laakso ve Poikkeus, 1998;Raikes ve diğerleri, 2006;Saracho, 2017;Shahaeian ve diğerleri, 2018;Vandermaas-Peeler ve diğerleri, 2011;Whitehurst ve diğerleri, 1988) empati gelişiminde (Aram ve Shapira, 2012;Tercanlı Metin ve Gökçay, 2014) ve bilişsel gelişimde (Hutton ve diğerleri, 2017a(Hutton ve diğerleri, , 2017bShahaeian ve diğerleri, 2018) önemli rol oynadığını göstermektedir.…”
unclassified